Viscoelastic properties of bronchial mucus after respiratory physiotherapy in subjects with bronchiectasis - Ramos, Ercy M. C. [UNESP]; Ramos, Dionei [UNESP]; Moreira, Graciane L. [UNESP]; Macchione, Mariangela; Guimaraes, Eliane T.; Rodrigues, Fernanda Maria M. [UNESP]; Lino de Souza, Altay Alves; Saldiva, Paulo H. N.; Jardim, Jose R. (Daedalus Enterprises Inc, 2015)
BACKGROUND: Previous studies have evaluated the effectiveness of postural drainage (PD), percussion (PERC), the coughing technique (CT), and other types of coughing in subjects with bronchiectasis. However, the application times of these techniques and the quality of the expectorated mucus require further study. The aim of our study was to evaluate the effectiveness of PD, percussion, CT, and huffing in subjects with bronchiectasis and assess the quantity and quality of bronchial mucus produced (measurement of wet and dry weight and determination of viscoelastic properties). METHODS: Twenty-two subjects with stable bronchiectasis (6 men; mean age: 51.5 y) underwent 4 d of experimental study (CT, PD+CT, PD+PERC+CT, and PD+huffing). The techniques were performed in 3 20-min periods separated by 10 min of rest. Before performing any technique (baseline) and after each period (30, 60, and 90 min), expectorated mucus was collected for analysis of viscoelasticity. RESULTS: A significant increase in the dry weight/wet weight ratio was found after 60 min of PD+PERC+CT (P = .01) and 90 min of PD+huffing (P = .03) and PD+PERC+CT (P = .007) in comparison with CT. PD+PERC+CT and PD+huffing led to the greatest removal of viscoelastic mucus at 60 min (P = .02 and P = .002, respectively) and continued to do so at 90 min (P = .02 and P = .01, respectively) in comparison with CT. An interaction effect was found, as all techniques led to a greater removal of elastic mucus in comparison with CT at 60 min (PD+CT, P = .001; PD+PERC+CT, P < .001; PD+huffing, P < .001), but only PD+PERC+CT and PD+huffing led to a greater removal of elastic mucus than CT at 90 min (P < .001 and P = .005, respectively). CONCLUSIONS: PD+PERC+CT and PD+huffing performed similarly regarding the removal of viscoelastic mucus in 2 and 3 20-min periods separated by 10 min of rest. PD+PERC+CT led to the greatest removal of mucus in the shortest period (2 20-min periods separated by 10 min of rest). (C) 2015 Daedalus Enterprises
Keywords: Bronchiectasis; Mucus; Viscosity; Elasticity; Cough; Physical therapy modalities